The relationship between lis pendens and exclusive agreed international jurisdiction in the law of the Hague Conference and Bosnia and Herzegovina - Poljić, Adis (Glasnik Advokatske komore Vojvodine, 2021)
The subject of the paper refers to the analysis of the realization of the will of the contracting parties in the law of the Hague Conference and Bosnia and Herzegovina. The exercise of the will of the Contracting Parties may be limited by the institute of lis pendens, which makes it impossible to conduct two proceedings between the same parties at the same time, giving priority to the first one, regardless of the agreed international jurisdiction. By contracting the jurisdiction of the parties, they decide which court will resolve their dispute, which is extremely important for the parties. Based on the analysis of the Hague Convention on Agreements on the Choice of Competent Court, it is concluded that preference is given to proceedings before the chosen court, with certain exceptions when the agreement of the parties will not apply. The law of Bosnia and Herzegovina applies the rules of lis pendens which may prevent the application of the agreement of the parties.